Interleukin-1 is associated with inflammation and structural lung disease in young children with cystic fibrosis - Montgomery, Samuel T.; Dittrich, A. Susanne; Frey, Dario; Mall, Marcus A. (Journal of cystic fibrosis, 2018)
Background - Little is known about the role of interleukin (IL)-1 in the pathogenesis of cystic fibrosis (CF) lung disease. This study investigated the relationship between IL-1 signalling, neutrophilic inflammation and structural lung changes in children with CF. - Methods - Bronchoalveolar lavage fluid (BALf) from 102 children with CF were used to determine IL-1α, IL-1β, IL-8 levels and neutrophil elastase (NE) activity, which were then correlated to structural lung changes observed on chest computed tomography (CT) scans. - Results - IL-1α and IL-1β were detectable in BAL in absence of infection, increased in the presence of bacterial infection and correlated with IL-8 (p<0.0001), neutrophils (p<0.0001) and NE activity (p<0.01 and p<0.001). IL-1α had the strongest association with structural lung disease (p <0.01) in the absence of infection (uninfected: p<0.01 vs. infected: p=0.122). - Conclusion - Our data associates IL-1α with early structural lung damage in CF and suggests this pathway as a novel anti-inflammatory target.